Analysis of the final destination of used or contaminated lubricating oil in Manaus - AM - Cardoso, Felipe Azevedo; Alves, Rodrigo Couto; Guimarães, Gabriel dos Anjos (Brazilian Journal of Production Engineering, 2023)
Solid waste generation is related to urbanization and population growth. One of the most worrying solid waste is Used or Contaminated Lubricating Oil (UCLO) due to its level of hazardousness. The present study sought to analyze the management of UCLO waste generated in a recycling company in Manaus-AM. On -site visits were made between June and July 2022 in a recycler, with the observation of the operation, questionnaire application and final destination process, as well as a diagnosis by pointing out the main observations and suggestions for improvements that can be implemented in the process of reverse logistics. Factors have been observed that hinders the final destination of UCLO. Also, it was possible to highlight the viability and importance of the refine process in the Amazon region. Posteriorly, rapid return measures were proposed for recycling and reverse logistics of UCLO. Finally, UCLO management contributes to the path of sustainability, as UCLO can be used infinite times, without providing any risk of contamination to the environment, contributing to a balance between the mode of operation and the development of society.